Use of a three-compartment model to evaluate the dynamics of cover crop residues - De Sa Pereira, Eduardo; Galantini, Juan Alberto; Duval, Matías Ezequiel (Taylor & Francis, 2023)
Cover crop (CC) residues protect the soil from erosion and their permanence on the surface is largely influenced by their biochemical constituents. In this study, the dynamics of CC residue decomposition by applying mathematical models was described. The kinetics of decomposition of residues was obtained from a laboratory incubation experiment. Three CC shoot residues were applied on the soil surface and incubated for 362 days (with eight sampling times). Oats and vetch residues decomposed the most than clover, where k values were 3.6 × 10− 3, 3.7 × 10− 3 and 5.3 × 10− 3 day−1, respectively. The three-compartment model (nonstructural carbohydrates, cellulose–hemicellulose and lignin) to simulate residue decomposition presented a close fit between simulated and measured data. The decomposition rate constant (k) of CC can be used to estimate how long residues will remain in the field and how they could affect soil organic carbon.